A structural study of the capsular antigen of Klebsiella serotype K43 - Aereboe, Michael (Rhodes University, Faculty of Pharmacy, Pharmacy, 1993)
This thesis presents a detailed chemical and spectroscopic determination of the capsular, polysaccharide K-antigen isolated from the Klebsiella bacterium, serotype K43 (culture #2482). The repeating unit of the capsular polysaccharide was found to be of the "3 + 2" repeating unit type. A uronic acid was found as part of a disaccharide side chain and the main chain of the polysaccharide was found to be composed of a neutral trisaccharide of mannose and galactose. The work forms part of an ongoing research interest in bacterial polysaccharides of this laboratory and now completes the structural elucidation of all the Klebsiella K-antigens, bar three antigens which were originally assigned to other laboratories. These data together with the respective serological characteristics of each serotype are available to the molecular biologist, and may result in the production of: vaccine(s) against Klebsiella infections, diagnostic products and novel carrier molecules enabling targeted drug delivery.
Keywords: Polysaccharides; Klebsiella; Antigens; Enterobacteriaceae